Fake news: um estudo sobre a necessidade de regulamentação e o Projeto de Lei nº 2.630/2020 - Souza, Fabiano Abrão Martins de Fraia (2023)
The present study addresses the theme of fake news, seeking a parallel in the Brazilian legal system, as well as in the spectrum of the philosophy of law. This theme, despite being old, has been in vogue since the 2016 US elections. Although in recent years it has been spread to the extreme by the media and social networks, the theme hides its essence and real objective from the general public. The present master's research has as its object of study a study on fake news and the importance of regulating Bill nº 2.630/2020. Therefore, it has the general objective: to show the true objective of Fake News, which is generally intended with the lies that are told in a mass manner and spread in an organized and premeditated way through messaging applications - which end up being replicated and reposted outside the world – often being compared to a viral disease that spreads very quickly, as well as presenting the need for regulation that such a phenomenon demands and requires. Therefore, the specific objectives of this research are: to present the basic premises of the theme, its nuances and curiosities; conceptually analyze the fake news, as well as how they are usually used, what the agents intend with the dissemination of fake news and what they can generate and have already generated in society as the final object of lies; recognize the laws in the Brazilian democratic state of law that deal with the subject, if they are sufficient to regulate the matter; recognize the importance of Bill No. 2,630/2020, which is being processed by the National Congress, as an equalizer to reduce the harm caused by the dissemination of false news. As a result, it is clarified that fake news negatively reflects on daily life and relationships, violating the right of personality in freedom of expression, harming honor, image, intimacy and privacy, with Bill No. 2.630/2020 an aid and collaborator with civil society to resolve or reduce the problem, changing the course of strategic issues of great importance to society as a whole